The Need To Use Geographic Information Systems In Air Traffic Control - et. al., Dilshod E. Eshmuradov, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the Republic of Uzbekistan, measures are widely carried out to assess the state of the telecommunications sector and the rational use of ICT based on GIS, the compilation and use of digital radio navigation graphic databases, the conduct of effective monitoring and automated air traffic control. The accuracy of ground-based radio navigation aids essentially depends on geodetic measurements, which are carried out in a certain coordinate system, and their final accuracy directly depends on the accuracy of the adopted coordinate base. Therefore, ensuring high accuracy of both measurements and their processing takes an especially important place in the construction of geographic information networks. However, the state geodetic network, if it is not systematically updated and improved, is gradually aging, loses some points, loses accuracy in some of its parts, esspecially due to modern movements of the earth's crust. air traffic. Special attention is paid to the possibilities of GIS in the compilation of radio navigation maps, the coordination of international flight control systems, the development of simulation models that allow efficient airport management.